Trauma system funding: implications for the surgeon health policy advocate - Saunders Lin; Christian Johnson; Frank Opelka; Amy Liepert (Trauma Surgery & Acute Care Open)
Background Trauma systems improve mortality for the most severely injured patients; however, these systems are managed by individual states with different funding mechanisms, which can lead to inconsistencies in the quality of care. This study compiles trauma system legislation and regulations of funding sources and creates a trauma funding categorization system. Such data help to inform the systems of trauma care delivery within and between states.Methods Online searches of state statutes were performed to establish the presence of legislative code to establish a trauma system, the presence of legislative code that funds these trauma systems, and the amount of funding that was allocated to each state’s trauma system in fiscal year 2016 to 2017. Following this, each state’s trauma system was contacted via email and telephone to further obtain this information.Results Specific state legislation creating a trauma system was identified in 48 states (96%). Data for categorization of trauma system funding were obtained in 30 states (60%). Of these 30 states, 29 have legislation funding their trauma systems. 17 states funded their trauma systems through general appropriations legislation, 10 states used percentages of fines from criminal and misdemeanor offenses, and 7 states used fees and taxes. New York state does not have any specific funding legislation. Individual state financial contributions to state trauma systems ranged from $55 000 to $25 899 450, annually.Discussion There is a limited amount of trauma system funding details available, and among these there is wide variation of funding source types and amounts allotted toward trauma systems. It is difficult to obtain and summate legislative information for use for surgical health policy advocacy efforts. Further study and method development to disseminate comprehensive and comparative legislative and regulatory data and information to physicians and other trauma system stakeholders are needed.Level of evidence III, economic and valued-based evaluation; analyses based on limited alternatives and costs; poor estimates.